Synthesis, Identification and Biological Study of New Pharmaceutical Model Based on Amino Acids with Some of Its Complexes - Mahmoud, Simaa Safaa; Khaleel, Asmaa Mohammed Noori (Iraqi Journal of Science, 2023)
The synthesis of the MBIB ligand by the reaction of the BIB ligand with methionine in 1:1 ratio, and the metal complexes with Ni(II), Cu(II), and Pt(IV) were described. All synthesized compounds were characterized using spectroscopic methods such as FT-IR, 1H NMR, UV-VIS, thermal analysis (TG and DSC), atomic absorption (AAS), elemental microanalysis (C.H.N.S), melting point (m.p.), magnetic susceptibility, molar conductivity measurements, and chloride content. All the complexes were electrolytes, and the suggested geometric shapes for the complexes were octahedral. The magnetic properties of the platinum complex were diamagnetic, while those of the nickel and copper complexes were paramagnetic. All synthesized compounds have good anti-biofilm properties against bacteria (Pseudomonas auroginosa, a gram-negative bacteria), except for C1(Ni), which is inactive against the same bacteria. In addition, the ligand was evaluated as an anti-cancer agent against human breast cancer (MCF-7), but its effectiveness has been shown to be less effective compared to metronidazole.